الأبحاث البيوطبية وتغير مفهوم الإنسان - زروخي, الدراجي (Université de M'sila, 2017)
Scientific research is characterized by rigor methodology and objectivity and requires a lot of attention and care. It calls for continuous efforts and great ability of imagination perseverance and self-control. But before the develloping the scientific approach in its current form mankind used another kind of thinking known philosophical thinking. If the scientific thinking is judged as organized and unified thinking this does not mean that philosophical thinking is unorganized. It is a thinking subject to logical standards and take into account the consistency of introductions with the final results. Moreover the philosophical thinking gives more freedom to the mind and less constrained by the standard and controls and it is characterized by a kind of totalitarianism. The separation of scientific thinking came after the maturity of scientific methods whichrationalized and quantified the phenomena and their interpretations. The maturuty of the scientific thinking comes from the succes of natural Sciences which dealt with realistic physical phenomena and it based on scientistic experimental approach as a way to understand and interpret physical phenomena. After the stunning success of the natural sciences some scientists and thinkers try the application of the experimental methods in the study of social phenomena which led to the separation between the Sociology of the philosophy. However the Sociology subjects differ from those of the natural sciences. they are more complex and interconnected and this is what made the scientific study of the social phenomena known several epistemological obstacles preventing the rationalization of the social phenomena driving a skepticism in the value of the science of Sociology and its ability to interpret social phenomena using only scientific explanation without the philosophical interpretation. or is it that social studies should return to the field of philosophy. Under these methodological problems a new challenges for humanities and social sciences have been found as a result of scientific and technical development. So what are these challenges ?
Keywords: dialectic social science canonical scientific rationalization methodology objectivity the philosophical thinking social phenomena.